Think Piece: Situating Education for Sustainable Development in southern African philosophy and contexts of social-ecological change to enhance curriculum relevance and the common good - Tichaona Victor Pesanayi; Rob O'Donoghue; Soul Shava (Environmental Association of Southern Africa, 2019)
The study opens with a brief review of how education in colonial southern Africa was steered by a succession of externally framed abstractions that have been implemented within the prevailing hegemony of western modernisation that dominated and marginalised indigenous cultures. It probes how, within an expanding functionalist framework, Education for Sustainable Development (ESD) has been similarly constituted as a proposition for implementation. Here the supposition is that implementing ESD as an intervention will transform education into an inclusive and collaborative pedagogy that will shape competences for participants to transform society towards a sustainable future. In an effort to explore the possibility of making a break from a succession of education imperatives functioning as 'salvation narratives' to put things right in Africa, the study explores ESD from a more situated and emergent vantage point within African landscapes, philosophy and cultural practices. This requires a shift from a view of ESD as a perspective to be brought in and enacted to foster change, to ESD as a situated engagement in education as a process where relevance is deliberated and brought out in quality education with high order skills. This perspective exemplifies working with a more fully situated framing of deliberative social learning for the common good. It is explored here to contemplate how socio-cultural processes of deliberative ethics and co-engaged reflexive processes of learning-led change might emerge. Here, also, using a capabilities approach might provide useful starting points for ESD as an expansive process of transformative social learning.